2014
DOI: 10.14776/kjpid.2014.21.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Syphilis: An Uncommon Cause of Gross Hematuria, Skin Rash, and Pneumonia

Abstract: Although congenital syphilis can be prevented with prenatal screening, the disease remains problematic. Currently, there are no cases that describe hematuria and pneumonia related to congenital syphilis. We report a case of congenital syphilis that involved nephrotic syndrome and pneumonia alba in a 22-day-old male infant whose mother did not receive adequate prenatal care. The congenital syphilis diagnosis was confirmed with a serologic test and the patient recovered with penicillin treatment. Clinical findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Eradication of the antigen after anti-syphilitic therapy may result in prompt disappearance of renal abnormalities and their non-recurrence ( 14 ). In a recent year, Shim et al ( 15 ) reported the CS infant with NS, however, the baby had typical skin lesion such as maculopapular rash, and desquamation. Although our patient fulfilled the criteria for congenial syphilitic nephropathy with unequivocal evidence of CS in the patient, evidence of syphilis in the mother, absence of any other etiology for CNS ( 14 ), he had no other symptoms of syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Eradication of the antigen after anti-syphilitic therapy may result in prompt disappearance of renal abnormalities and their non-recurrence ( 14 ). In a recent year, Shim et al ( 15 ) reported the CS infant with NS, however, the baby had typical skin lesion such as maculopapular rash, and desquamation. Although our patient fulfilled the criteria for congenial syphilitic nephropathy with unequivocal evidence of CS in the patient, evidence of syphilis in the mother, absence of any other etiology for CNS ( 14 ), he had no other symptoms of syphilis.…”
Section: Discussionmentioning
confidence: 99%